Resistensi Treponema pallidum terhadap Makrolida Sebagai Pengobatan Alternatif Sifilis - Desy Ariani Gultom (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Treponema pallidum (T. pallidum) is a pathogen that causes syphilis, which is transmitted through contact with active lesions of a sex partner or an infected pregnant woman to her fetus. Despite various aggressive efforts and pharmacological treatments, syphilis has persisted and continues to be a health problem, even experiencing an increase in the prevalence of the disease in recent years. This article is based on literature studies on various research published online, especially on Google Scholar, ScienceDirect, Scopus, Pubmed, and other scientific journals. The studies were then synthesized into comprehensive information regarding specific resistance mechanisms of T. pallidum bacteria to several antibiotics. Macrolide, especially azithromycin, is an alternative treatment that is most often used in the treatment of syphilis in addition to first-line antibiotics, benzathine penicillin G injection. The use of its single oral dose, its effectiveness equivalent to penicillin, cost-effectiveness, and rare side-effect profile made azithromycin widely used in the treatment of syphilis in various regions throughout the world until treatment failures were reported. The mechanism of resistance to macrolides occurs due to modification of the antibiotic target site (binding site) caused by mutations in the 23S rRNA gene. The increase in cases and the emergence of clinically significant resistance to alternative antibiotics in some countries emphasize the urgent need for vigilance. Knowledge and understanding of the resistance mechanism of Treponema pallidum to antibiotics, especially the macrolides group, is essential in line with the increasing resistance of Treponema pallidum to antibiotics globally.